(untitled) (Innovative professional education, 2023)
The expediency of using training in the system of methodical work of a professional (vocational) education institution is substantiated. The functions and components of the training are characterized, the most effective methods of training for conducting trainings with teachers of professional (vocational) education institution are determined. The structure of methodical training is described and the characteristics of its main stages are given.